2015
DOI: 10.1002/da.22327
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy for Hoarding Disorder: A Meta-Analysis

Abstract: CBT is a promising treatment for HD, although there is significant room for improvement. Results are discussed in terms of treatment refinement for HD, and additional moderator variables are suggested for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
169
2
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(195 citation statements)
references
References 70 publications
17
169
2
7
Order By: Relevance
“…The IBT showed overall positive changes and a clinically significant diminution of hoarding symptoms in the range previously reported for CBT [27]. The effect of IBT remained stable at 6-month follow-up for 100% of cases who had shown clinically significant post-treatment hoarding improvement; there was no difference between post-treatment and 6-month followup hoarding scores.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The IBT showed overall positive changes and a clinically significant diminution of hoarding symptoms in the range previously reported for CBT [27]. The effect of IBT remained stable at 6-month follow-up for 100% of cases who had shown clinically significant post-treatment hoarding improvement; there was no difference between post-treatment and 6-month followup hoarding scores.…”
Section: Discussionsupporting
confidence: 64%
“…In geriatric patients, however, CBT did not demonstrate any significant effect [25]. Jónsson A meta-analysis of 10 trials of CBT in HD, performed by Tolin et al [27] showed reliable and clinically significant change in HD patients of 40.12% for functional impairment and 25.44% for clutter. Williams [28] reported effect sizes, limits and challenges of different option in HD treatment [28].…”
Section: Pharmaceutical Treatmentmentioning
confidence: 99%
“…Build the mental muscle of your mind. Anita et al [5] study that the rested mind that the entire beneficial cycle starts. In Psychoanalytical language meditation helps in conquering the neurotic tendencies and makes the mind peaceful and happy.…”
Section: Signsmentioning
confidence: 99%
“…However, when the CBT model has been tested in more varied clinical samples (such as in a geriatric hoarding), evidence indicates attenuated outcomes (Ayers et al, 2011), without necessary population specific alterations (Ayers et al, 2014). A recent meta-analysis of HD with the CBT treatment model (Tolin, Frost, Steketee & Muroff, 2015) found large effect sizes for symptom severity reductions, rates of clinically significant change were lower (24-43%).…”
Section: Introductionmentioning
confidence: 99%